2022
DOI: 10.1017/s1368980022000489
|View full text |Cite
|
Sign up to set email alerts
|

Food promoted on an online food delivery platform in a Brazilian metropolis during the coronavirus disease (COVID-19) pandemic: a longitudinal analysis

Abstract: Objective: To analyse food advertised on an online food delivery (OFD) platform during 16 weeks of the COVID-19 pandemic in Brazil. Design: Longitudinal study. We randomly selected foods advertised on the OFD app’s home page, classifying the food items into water; natural juices and smoothies; vegetables; fruits; traditional meals and pasta; ultra-processed beverages; ice cream and candies, and salty packaged snacks; sandwiches; savoury snacks; and pizza. We also registered the marketing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…For example, by saving time spent on food shopping and home cooking, OFD may also reduce physical activity time, resulting in an increase in health problems associated with sedentary lifestyle [ 8 , 13 , 14 ]. Moreover, due to lack of information or labeling, it is difficult to guarantee the nutritional quality of OFD food [ 15 17 ], not to mention meeting the individualized nutritional needs [ 18 , 19 ]. These may lead to a negative impact on public health.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, by saving time spent on food shopping and home cooking, OFD may also reduce physical activity time, resulting in an increase in health problems associated with sedentary lifestyle [ 8 , 13 , 14 ]. Moreover, due to lack of information or labeling, it is difficult to guarantee the nutritional quality of OFD food [ 15 17 ], not to mention meeting the individualized nutritional needs [ 18 , 19 ]. These may lead to a negative impact on public health.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Stephens et al (2020) [ 14 ] suggested that standardized online ordering of fast food similar to pizza was popular among OFD consumers in the US. Horta et al (2022) [ 19 ] found that traditional meals and pasta set meals 4 were the food items most frequently pushed to consumers by Brazilian OFD platforms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of food delivery services may contribute to a sedentary lifestyle, increasing the risk of adverse health outcomes [ 62 ]. Food safety and health issues have raised people’s concerns [ 91 , 92 ]; however, online food delivery platforms always seem to promote unhealthy food [ 93 ]. During the pandemic, people’s diets changed, especially as unhealthy diets increased [ 45 , 93 , 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may include, for example, finding patterns in use across populations and running trials on when and how to prompt and offer different outlets and items to trigger further and higher-value purchases. These goals are opaque to individual users of the services, and may be at odds with public health goals [ 48 , 49 ]. An Australian initiative where researchers partnered with young ‘citizen scientists’ to track the promotion of unhealthy food, alcohol and gambling that they saw on their social media feeds is an example of efforts to expose the ‘dark marketing’ strategies that target consumers [ 50 ].…”
Section: Discussionmentioning
confidence: 99%